A TEST FOR MYOCARDIAL INFARCTION—The Present Status of the Use of Serum Lactic Acid Dehydrogenase - Wilson, H. T. (1958)
Determination of the amount of lactic acid dehydrogenase in the blood has been demonstrated as a useful aid in the diagnosis of myocardial necrosis. The reliability of the test and the time element of the appearance and disappearance of the enzyme in the blood give it advantages over transminase determinations. In addition there appears to be a correlation of lactic acid dehydrogenase content with metastatic carcinoma. The levels of the substance correlate with the presence or absence of metastatic lesions and also with the extent of the metastasis. Few other clinical states are associated with increased levels of this enzyme, and in most instances the few that are can be excluded by other reliable criteria.